2013
DOI: 10.1345/aph.1s003
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Heart Rate Changes Associated with Levalbuterol and Racemic Albuterol in Pediatric Cardiology Patients

Abstract: Racemic albuterol and levalbuterol were associated with increased heart rate in pediatric cardiology patients. This increase was found to be equivalent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In patients with CHD, the RS group experienced a mean heart rate increase of 6.6 beats/min compared to 6.3 beats/min in the LS group (which was a statistically equivalent increase). 21 This study is important because it suggests that both racemic salbutamol and levosalbutamol increase heart rates but were equivalent not only in general population, also in children with congenital heart disease.…”
Section: Studies and Resultsmentioning
confidence: 85%
“…In patients with CHD, the RS group experienced a mean heart rate increase of 6.6 beats/min compared to 6.3 beats/min in the LS group (which was a statistically equivalent increase). 21 This study is important because it suggests that both racemic salbutamol and levosalbutamol increase heart rates but were equivalent not only in general population, also in children with congenital heart disease.…”
Section: Studies and Resultsmentioning
confidence: 85%
“…The lowerpercentile HRs are most likely to reflect the times when the subject was asleep (33). Moreover, studies of albuterol use in pediatric patients have shown only small increases in HR with single dose of albuterol, and with treatment of asthma exacerbations, HR declines (34)(35)(36). Finally, the RF model possesses the capacity to predict asthma events before report of symptoms, suggesting changes in physiology before either the use of albuterol or perception of symptoms by the subject.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29][30][31][32] These studies have reported conflicting results. A meta-analysis of clinical studies evaluating levalbuterol versus albuterol for the treatment of acute asthma patients (pediatric and adult) concluded that levalbuterol is not superior to albuterol in terms of safety or efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies evaluating levalbuterol in pediatric or critically ill patients have reported results similar to the findings of our analysis. 32,37 Additionally, our study only evaluated the short-term use of inhaled nebulizers for treatment of acute exacerbations. Many patients use metered-dose inhalers containing levalbuterol or albuterol on a fairly regular basis for chronic disease control.…”
Section: Comparative Data On Total Treatment Costs ($) Stratified By mentioning
confidence: 99%